2020
DOI: 10.1002/acr2.11133
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Operational Capacity and Reducing Costs of Rituximab Administration: A Costing Analysis

Abstract: Objective. Originator intravenous rituximab is an important rheumatology treatment but is costly, and administration requires several hours. Because biosimilar rituximab may cost less and subcutaneous rituximab requires a shorter visit, both may reduce costs and increase treatment capacity (infusions per year).Methods. We implemented time-driven activity-based costing (TDABC), a method to assess costs and opportunities to increase capacity, throughout the care pathway for 26 patients receiving a total of 30 ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Similar studies conducted outside of the US would also be useful to provide perspective on how practice varies internationally, especially given the cost of RTX therapy. 11 In comparison with CYC use, we observed that MTX was more commonly used to treat AAV at various timepoints in the clinical course of this cohort. This may reflect that patients with AAV in RISE have less severe disease and/or that providers and patients prefer MTX over alternative options because of different side effect profiles or comfort level.…”
Section: Discussionmentioning
confidence: 77%
“…Similar studies conducted outside of the US would also be useful to provide perspective on how practice varies internationally, especially given the cost of RTX therapy. 11 In comparison with CYC use, we observed that MTX was more commonly used to treat AAV at various timepoints in the clinical course of this cohort. This may reflect that patients with AAV in RISE have less severe disease and/or that providers and patients prefer MTX over alternative options because of different side effect profiles or comfort level.…”
Section: Discussionmentioning
confidence: 77%
“…23 We estimated the cost of services related to mAb PEP administration as $114 based on a time-driven activity-based cost estimate reported for outpatient subcutaneous administration of another medication adjusted to 2020 US$ (appendix page 3). 24…”
Section: Methodsmentioning
confidence: 99%
“…23 We estimated the cost of services related to mAb PEP administration as $114 based on a time-driven activity-based cost estimate reported for outpatient subcutaneous administration of another medication adjusted to 2020 US$ (appendix page 3). 24 Analytical methods: To estimate the cost and impact of PEP, we used an analytical model summarized by a decision tree (Figure 1) with a choice node for mAb PEP followed by chance nodes for symptomatic infection, hospitalization, and death. We used demographic data from confirmed cases of COVID-19 to identify households where PEP would be indicated, and then used demographic data on household structure to identify the age, sex, and race of the household members who could receive mAb PEP.…”
Section: Methodsmentioning
confidence: 99%
“…The cost of inebilizumab for the first year of treatment is approximately $393,000 USD for three infusions (two loading doses, followed by a single 300 mg dose 6 months later) and $262,000 USD per year, for two yearly doses [ 25 ]. In contrast, rituximab and biosimilars are relatively modestly priced: $19,452 USD for two 6-month infusions per year) [ 30 ].…”
Section: Long-term Management: Precision Versus Personalized Medicinementioning
confidence: 99%